Remineralisation of enamel white spot lesions pre-treated with chitosan in the presence of salivary pellicle. (May 2018) - Zhang, Jing; Lynch, Richard J.M.; Watson, Timothy F.; Banerjee, Avijit
Abstract: Objective: To investigate the remineralisation of chitosan pre-treated enamel white spot lesions (WSLs) by bioglass in the presence of the pellicle layer. Methods: 50 artificial enamel white spot lesions were created by acidic gel. Two lesions were used to investigate the formation of the pellicle layer by treating with human whole saliva for 3 min. 48 lesions were assigned to 6 experimental groups (n = 8): (1) bioactive glass slurry, (2) bioactive glass containing polyacrylic acid (BG + PAA) slurry, (3) chitosan pre-treated WSLs with BG slurry (CS-BG), (4) chitosan pre-treated WSLs with BG + PAA slurry (CS-BG + PAA), (5) "standard" remineralisation solution (RS) and (6) de-ionised water (negative control, NC). Remineralisation was carried out using a pH-cycling model for 7 days. Before each treatment using remineralising agents, 3-min pellicle was formed on lesions' surfaces. Mineral content changes, surface and subsurface microhardness and ultrastructure were evaluated by Raman intensity mapping, Knoop microhardness and scanning electron microscopy, respectively. Data were statistically analysed using one-way ANOVA with Tukey's test ( p < 0.05 is considered as significant). Results: Despite the heterogeneously formed pellicle layer, all groups showed an increase in surface mineral content after pH-cycling. Chitosan pre-treatment enhanced the subsurface remineralisation of WSLs using bioglass as both pre-treated groups showed greater surface and subsurface microhardness compared to NC. CS-BG exhibited denser subsurface structure than BG, while in CS-BG + PAA the crystals were bigger in size but resemble more enamel-like compared to BG + PAA as shown in SEM observations. Remineralisation of RS was limited to the surface as no significant subsurface changes of mechanical properties and structure were found. Conclusions: Chitosan pre-treatment can enhance WSL remineralisation with bioglass biomaterials when a short-term salivary pellicle is present. A further investigation using a long-term pH-cycling model with mature pellicle is suggested with regards to clinical application. Clinical significance: Chitosan pre-treatment has the potential in clinical application to remineralise subsurface lesions to achieve lesion consolidation.